Relative Effectiveness of Efficiency Criteria for Portfolio Selection - Levy, Haim; Hanoch, Giora (Journal of Financial and Quantitative Analysis, 1970)
Individual decisions about investment may be regarded as choices among alternative probability distributions of net returns. It is assumed that these distributions are completely known and independent of initial wealth positions, and that individuals determine the preferred portfolio of investment in accordance with a given, consistent set of preferences.